1999
DOI: 10.1046/j.1365-2141.1999.01405.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood progenitor cell (PBPC) counts during steady‐state haemopoiesis enable the estimation of the yield of mobilized PBPC after granulocyte colony‐stimulating factor supported cytotoxic chemotherapy: an update on 100 patients

Abstract: Summary. Peripheral blood progenitor cells (PBPC) can be mobilized using chemotherapy and granulocyte colonystimulating factor (G-CSF). We and others previously reported a correlation of steady-state PBPC counts and the PBPC yield during mobilization in a small group of patients. Here we present data on 100 patients (patients: 25 nonHodgkin's lymphoma (NHL), five Hodgkin's disease, 35 multiple myeloma (MM), 35 solid tumour) which enabled a detailed analysis of determinants of steady-state PBPC levels and of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 21 publications
3
52
0
1
Order By: Relevance
“…However, this high-dose chemotherapy with BMT was not successful in patients who were experiencing a second disease recurrence or who were cisplatin refractory. 31 We used PBSCT 32 to support high-dose chemotherapy in three patients. Three patients treated with high-dose chemotherapy were alive and disease free after 73, 52, and 25 months, respectively (Table 3).…”
Section: Nsgctmentioning
confidence: 99%
“…However, this high-dose chemotherapy with BMT was not successful in patients who were experiencing a second disease recurrence or who were cisplatin refractory. 31 We used PBSCT 32 to support high-dose chemotherapy in three patients. Three patients treated with high-dose chemotherapy were alive and disease free after 73, 52, and 25 months, respectively (Table 3).…”
Section: Nsgctmentioning
confidence: 99%
“…Fruehauf et al 21 reported measuring steady-state peripheral blood progenitors as a means to estimate the yield after combined chemotherapy and G-CSF mobilization. It may be possible to monitor the level of peripheral blood progenitors before and during mobilization as a guide to dose modification of HGF.…”
Section: Discussionmentioning
confidence: 99%
“…73 Older age was associated with poor autologous mobilization in some patient groups, 30,74,75 but not in others. 74,76 Even though some donors with predictors of poor mobilization respond quite well to mobilizing therapies, 77 poorly mobilizing autologous donors are assumed to have sustained an injury to the hematopoietic stem cell system that is responsible for the poor effect (see Table 4). In support of this premise, autologous donors with breast cancer who had received more chemotherapy and radiation or had tumor metastases in the marrow also had fewer stem/progenitor cells in apheresis products collected during steady state than donors who were less heavily pretreated and had no marrow metastases.…”
Section: Autologous Donorsmentioning
confidence: 99%